Fem simulation of static and dynamic tensile test - Yeo, Wei Min (Nanyang Technological University, 2017)
Split Hopkinson Tensile Bar (SHTB), an adaptation from the Split Hopkinson Pressure Bar (SHPB), is a commonly used setup for researchers and engineers to investigate a material’s mechanical properties and behavior when it is subjected to high strain rates. The technique has evolved over the years from a single continuous bar to 2 bars placed in series. The behaviour of the material will then be recorded on an oscilloscope for further analysis. This report focuses on the study of the mechanical properties of Aluminum Alloy 6061-T6 under quasi-static and high strain rate conditions. The entire quasi-static and SHTB setup will be modelled in SolidWorks modelling software and then ported over to ANSYS Mechanical APDL Workbench coupled with LS-DYNA for Finite Element Analysis (FEA) of the entire process. Running simulations on the FEA software, as compared to performing the actual SHTB experiment, is much more cost effective when it comes to analysing the material’s mechanical properties. The Stress vs Time, Strain vs Time and Stress vs Strain data will be compared to reputable journals and papers to validate the results. In the following simulations, the incident bar, transmitter bar, striker bar, specimen and also the shock-absorbing portion of the jig has been modelled to scale to eliminate irregularities between the simulation and actual experiment. Simulations will be performed with different configurations and permutations to get the results as close as possible to the actual experiment. An investigation will also be carried out to understand the effects of imperfect manufacturing on the stress-strain relationship.